ANALYSIS OF ADDRESS TERMS IN JUSTICE LEAGUE MOVIE - Fitri Ventalia; Ance Jusmaya (BASIS (Bahasa dan Sastra Inggris), 2020)
The aim of this research was to analyze the type and reason of address terms in WhatsApp group of Putera Batam University Justice League (2017) movie. This research is descriptive qualitative research. The research used observational method non-participatory technique to collect the data. The data was analyzed by applying the theory of Wardaugh (2010). The results found that the type of address terms were 8 data in first name (FN) in Man, Alfred, Diana, Barry, Howard, Silas, Bruce, Victor, 2 data in last name (LN) in Allen, Lane, 2 data in title (T) in Queen, Soldiers, 1 data in title plus last name (TLN) in Ms. Prince, 4 data in pet name (PN) in Aquaman, Batman, Cyborg, Superman and 3 data in kinship term (KT) in Dad, Mother, Child. The research also found the reasons of address term with 12 data in intimacy in Ma, Children, Diana, Man, Victor, Arthur, Barry, Alfred, guys, Bruce, Mom, Superman, 5 data in power differential in Mr. Wilson, Master Wayne, ma'am, insects, Luthor and 3 data in equality in Clark, Steppenwolf and Kal-El. Based on the results, it can be concluded that first name (FN) is the most found type of address term and intimacy is the most in reason of address term.